(untitled) (Research, Society and Development, 2024)
Introduction: Sporotrichosis is a fungal disease, caused by Sporothrix schenckii, characterized as one of the main cutaneous fungal infections and Brazil is an endemic area for the disease, mainly affecting the adult age group, and rarely children. The disease is transmitted through contact with contaminated waste inoculated onto damaged skin or mucosa. The diagnosis is clinical and can be complemented by tests. Objective: To report a pediatric clinical case of sporotrichosis in a patient under 2 years of age at the Hospital Universitário Maria Aparecida Pedrossian (HUMAP). Methodology: It is an observational, descriptive and analytical case report, based on data collection through physical and electronic medical records through HUMAP’s own system, all of which were obtained after approval by the Research Ethics Committee. Results: Female patient, 1 year and 5 months old, 15 days ago with a single papular lesion on the left upper limb that evolved into an ulcer with progressive size, clear bottom and raised edges. Initially, he was diagnosed with cutaneous Leishmaniasis and started on Glucantime, with partial improvement. During hospitalization, growth of Sporothrix was identified, and therapy was changed to Liposomal Amphotericin B. The patient evolved with significant clinical improvement of the lesion. Conclusion: Ulcerative lesions have multiple diagnoses, and the increase in infectious-parasitic diseases has highlighted flaws in preventive actions and highlighted the importance of ongoing education for health professionals and the population in order to break transmission chains.